Faktor-Faktor Pengembangan Kapasitas Dalam Pengelolaan Keuangan Daerah: Studi Kasus Unit Pelaksana Teknis Laboratorium Pengelolaan Keuangan Daerah Jawa Timur - Basnawi, Choiriyah (Universitas Airlangga, 2021)
This study aims to examine the factors that influence the development of human resource capacity in regional financial management through the Clinic Center by the Technical Implementation Unit of the East Java Regional Financial Management Laboratory. This research is motivated by the many problems that arise in regional financial management due to the low capacity of human resources in financial management. To overcome these problems, the East Java Provincial Government through BPKAD created an Innovation Regional Financial Management Laboratory which was later shortened to